2022
DOI: 10.1098/rsbl.2021.0328
|View full text |Cite
|
Sign up to set email alerts
|

Increasing numbers of killer whale individuals use fisheries as feeding opportunities within subantarctic populations

Abstract: Fisheries can generate feeding opportunities for large marine predators in the form of discards or accessible catch. How the use of this anthropogenic food may spread as a new behaviour, across individuals within populations over time, is poorly understood. This study used a 16-year (2003–2018) monitoring of two killer whale Orcinus orca subantarctic populations ( regular and Type-D at Crozet), and Bayesian multistate capture–mark–recaptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Anecdotal evidence suggests that these interactions have continued and may have spread to or from other regions. Although some studies have shown that associations with fisheries have benefitted whales (e.g., killer whales in the Crozets; (Amelot et al 2022;Tixier et al 2017), the energetic implications and risks of interactions for cetaceans described here are unknown and need further study.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Anecdotal evidence suggests that these interactions have continued and may have spread to or from other regions. Although some studies have shown that associations with fisheries have benefitted whales (e.g., killer whales in the Crozets; (Amelot et al 2022;Tixier et al 2017), the energetic implications and risks of interactions for cetaceans described here are unknown and need further study.…”
Section: Discussionmentioning
confidence: 93%
“…Open water may make it easier for whales to detect (i.e., either visually or acoustically) and catch escaping fish that may also be disoriented or disabled. The energetic costs of deep vs. shallow diving and differences in prey encounter rates compared to natural foraging may contribute to whales continuing and potentially increasing their associations with fishers in this and other areas (Amelot et al 2022). Karpouzli & Leaper's (1997) earlier research on interactions between sperm whales and benthic trawlers in the same area as this study showed a pronounced difference in sighting rates with trawling phases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations